Paradigms and Fallacies: Rethinking Northeast Asian Security - Park, Hun Joo (KDI School of Public Policy and Management, 2005)
This paper examines the changing characteristics of the fundamentally distrustful, conflict-ridden, and power and interest-centric international politics in Northeast Asia and their implications for the region's stability especially in the post-Cold War era. No doubt that the power and interest-centric realist paradigm maintains its explanatory dominance in capturing the lack of reconciliation or institutionalization of regional cooperation both in postwar and post-Cold War Northeast Asia. When it comes to prescribing for the lack of institutionalized multilateralism or security cooperation, however, the analytic power of realist perspective becomes sterile. It is so because realists assume the values, preferences and goals of the units or nation states as largely fixed or determined by the anarchical international system. Such a realist paradigm has frequently led to a self-fulfilling prophecy: as if inevitably pressured by the system, states end up pursuing their narrow and myopic national interests, further exasperating security dilemma. The paper argues that to help prevent the security dilemma from spiraling into a slippery and perilous path of arms competition in Northeast Asia requires the concerned states and their policymakers to switch their realist assumptions, redefine their self-interests, and adopt an international society framework which builds on reality.
Keywords: Northeast Asian Security; Paradigms; Foreign policy; Military Spending; The post-Cold War era